The metaphorical image in the poetry of Dabel Al-Khuzai, a rhetorical and analytical study (Journal of the College of Basic Education, 2022)
Debel Al-Khuzai's poetry was distinguished by the clear and distinctive presence of the graphic image in it, which reflects the fertility of the poet's imagination and his mastery of language in a great way. However, most of this poetry has been lost and has not beenThose that have come down to us are of interest to researchers and scholars, because of his political positions on the events of history, his strong defense of them, and his satire of his opponents (1), as well as his blasphemous style of satire, but he is the owner ofSober, traditional poetic approach characterized by elegance of style and ingenuity of visualization, and because this poet did not get his due from study and analysis despite the quality of his poems, this research came to study the graphic image inHis poetry, and we limited the study to the poetry attributed to the poet unanimously. From Khuza’a, he was born in 148 AH and died in 246 AH. It was said that Da’bal was called Ibn Ali Al-Khaza